Influence of Thermal Treatment on Fracture Due to Cyclic Fatigue of Rotary Files - Méndez-González, María Verónica; Pozos-Guillén, Amaury; Betanzos-Juárez, María Concepción; Izquierdo-Orozco, Alejandra; Gaitán-Fonseca, César; Escobar-Barrios, Vladimir Alonso; Gutiérrez-Sánchez, Mariana (Odovtos - International Journal of Dental Sciences, 2025)
The objective of this study aimed to assess the cyclic fatigue fracture of ZenFlexTM, ProTaper GoldTM, and HyFlexTM. EDM rotary files in simulated curved canals, along with evaluating their physicochemical properties and thermal behavior. A total of 69 instruments from three different NiTi rotary file systems were utilized: ProTaper GoldTM (08/25), HyflexTM EDM (08/25), and ZenflexTM (06/25). The analysis consisted of four phases: Phase 1 involved SEM observation to detect manufacturing defects; Phase 2 focused on cyclic fatigue-induced fracture in a curved canal with a 60° radius of curvature of 2 mm and a diameter of 1.5 mm; Phase 3 encompassed SEM observation of the fractured fragment and obtaining a fractographic study; Phase 4 included physicochemical characterization, such as equiatomic relationships by Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES), phase transformation by DSC, crystalline structure by X-ray diffraction, and morphological analysis by SEM. Microcracks and defects were observed on cutting edges of ZenFlexTM and ProTaper GoldTM files. The mean cycles to fracture were 2814.50±161.58, 2649.94±120.93, and 1362.89±88.33 for HyFlexTM, ZenFlexTM, and ProTaper GoldTM, respectively. Moreover, different phase transition temperatures were noted, with ZenFlexTM in the austenite phase, ProTaper GoldTM in martensite, and HyFlexTM in the R phase at room temperature, as corroborated by X-ray diffraction. Additionally, a quasi-equimolar relationship was observed for the different systems, with ZenFlexTM exhibiting a reduced helical angle, followed by HyFlexTM and ProTaper GoldTM. ZenFlexTM files demonstrated greater resistance to cyclic fatigue, which appeared to be attributed to their physicochemical properties, heat treatment, and design.